Design and Development of a Realistic Mathematics Education (RME)-Based E-Module on Triangle Concepts - Agus Maqruf; Tatang Herman; Elah Nurlaelah; Muhamad Zulfikar Mansyur; Dwi Maulida Sari (Pendidikan Matematika UNIMOR, 2026)
In training students to be able to solve problems logically and systematically, there is a need for learning media. Digital learning media that covers a wide range of subject matter nowadays is e-modules. Several studies have stated that the e-modules needed in mathematics learning are e-modules that are closely related to students' daily lives so that they are easy and practical to learn or in mathematics education it is known as Realistic Mathematics Education (RME). The research method used is the Richey and Klein Design and Development model with three stages, namely design, production and evaluation. The research was conducted at one of the junior high schools in Bandung City. The research instrument is intended for experts as validators and students as users The results indicate that through the stages of design, production, and evaluation, the RME-based e-module on triangle material was successfully designed and developed as a highly feasible learning resource for junior high school students in Indonesia. Expert validation showed an overall score of 90.3 percent categorized as very feasible, while student responses reached 86.9 percent also categorized as very feasible, confirming both its effectiveness and usability while providing valuable input for future refinement and wider development of the e-module.